(untitled) - Stopka, Ondrej; Sulgan, Marian (Doprava a spoje, 2012)
The paper deals with the general characteristics of freight villages (public logistics centers) and then outlines the construction support of the freight villages and intermodal terminals in the Slovak Republic and the Czech Republic. There is also shown the formation of logistics centers abroad, especially in Germany. There are described different methods of public freight villages' allocation at the end of the article.